Concerning the closeness of the form of Sufi Kashkul and the Slavic boats - Shkolna, Olga V.; Sosik, Olha D.; Barbalat, Oleksandra V.; Buihasheva, Alla B.; Zaitseva, Veronika I. (Linguistics and Culture Review, 2021)
The article deals with investigating the resemblance between the kashkul shape from the collection of the Istanbul Museum of Islamic and Turkish Art and the Slavic type of longship. The specified item is now being kept in the exposition of the specified collection as an item of the Sefevidian era period of the early 17th century under the inventory number 2960. The typological analysis of its shape, peculiarities of the use of similar items in the Orthodox tradition of the Old Rus, Byzantium, separate countries of the Christian world and Scandinavia prove the closeness of this item to the shapes that were common in the Orthodox society. Analysis of the item decoration, the method of its manufacture allows us to assume the contribution of Islamic craftsmen, possibly Persian, to casting of this artefact. The study results are reduced to the basic hypothesis that the object designated in the exposition of the Istanbul Museum of Islamic and Turkish Art called kashkul (a bowl for the poor or a container for alms) has a shape of a golden longship that was in common use between the 10th and 14th centuries in the Kyivan Rus-Byzantine tradition.